An Analysis of Using Duolingo Application in Improving Students’ Vocabulary Mastery at 10th Grade of SMA YADIKA Bandar Lampung - Desi Derina Yusda; Deri Sis Nanda; Tara Lusiana Mahdi Pratiwi; Haninun Haninun (BEYOND LINGUISTIKA (Journal of Linguistics and Language Education), 2020)
Pratiwi, (2020) An Analysis of Using Duolingo in Improving Students’ Vocabulary Mastery of 10th Grade at SMA YADIKA Bandar Lampung SMA YADIKA Bandar Lampung is one of the many schools in Bandar Lampung, researchers found several problems during observation. Some students said that they liked learning English but they found it difficult to express their skills due to lack of vocabulary, and the learning techniques used were still difficult to apply with this phenomenon. Teachers should use a lot of media, but in reality, the teacher only focuses on textbooks and manuals, teachers must be able to make students more eager to learn English and not make students stress when learning English. In this study, researchers used qualitative methods, precisely descriptive qualitative. The purpose of this study was to obtain evidence about how to use the Duolingo application in students' vocabulary mastery. The data source of this research is a video documentation of the learning process. The text is taken from interviews with students and students' opinions by distributing a list of questions. The results showed that the use of Duolingo Application as a Media in mastering the vocabulary of tenth-grade students at SMA YADIKA Bandar Lampung, it can be concluded that Duolingo Application has had a positive influence, this can be seen from the increased motivation, and students' Vocabulary Mastery; and the Duolingo Application has strengths namely Learning Through Technology, Language Courses, Duolingo Application Content, and Free registration and then its weaknesses, there are disadvantages of the Duolingo Application namely the Internet, Translations, and Features. So, it can be concluded that the Duolingo Application directly has a positive effect on tenth graders at Bandar Lampung YADIKA High School in vocabulary mastery.